Street Vendors Hypergrowth: Consequence of Uncontrolled Urbanization In Semarang City - Sariffuddin, Sariffuddin; Wahyono, Hadi; Brotosunaryo, Brotosunaryo (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2017)
This paper aims to understand the role of urbanization to street vendors emerging. In the case of Semarang, more than 54% Semarangâs street vendors come from its hinterlands. These sectors turn to development dichotomy that have a positive and negative impact. Positively, this area becomes resilience economy people. In the negative side, more than 60% vendors make their stall in the public space. This research used a mix-method approach taking 271 samples, Focus Group Discussion (FGD) and in deep interviews. From this study, it can be concluded that urbanization had led to the outbreak of street vendors through (1) rural-urban migration, and (2) the social change as a result of gentrification. Working as street vendors turned out to be an alternative way of life to adapt to global economic uncertainty. Also, there are 71.6% of street vendors open their stalls in 2003-2009, or about 6-7 years after the monetary crisis (1997). It shows that the financial crisis is not the primary trigger for the outbreak of street vendors. Another interesting finding is that there is a new phenomenon in the form of the intervention of the middle class who took part in this business.